Effects of Probiotic Bacteria Lactobacillaceae on the Gut Microbiota in Children With Celiac Disease Autoimmunity: A Placebo-Controlled and Randomized Clinical Trial - Oscarsson, Elin; Håkansson, Åsa; Andrén Aronsson, Carin; Molin, Göran; Agardh, Daniel (Frontiers in Nutrition, 2021)
Disturbances of the gut microbiota may influence development of various autoimmune diseases. This study investigated the effects of supplementations with the probiotic bacteria Lactiplantibacillus plantarum HEAL9 and Lactocaseibacillus paracasei 8700:2 on the microbial community in children with celiac disease autoimmunity. Included were 78 genetically predisposed children for celiac disease with elevated levels of tissue transglutaminase autoantibodies (tTGA) signalling for ongoing celiac disease autoimmunity. Among those children, 38 received placebo and 40 received the probiotic supplement daily for six months. Faecal and plasma samples were collected at baseline and after 3 and 6 months, respectively. Bacterial community was investigated with 16S rRNA sequencing and terminal restriction fragment length polymorphism (T-RFLP) and tTGA levels were measured in radiobinding assays. In children that received probiotic supplementation, the relative abundance of Lactobacillaceae increased over time while it remained unchanged in the placebo group. There was overall no correlation between on tTGA levels and bacterial genus except for a positive correlation between Dialister and IgG-tTG in the Probiotic Group. The abundance of specific bacterial amplicon sequence variant (ASV:s) changed during the study in both groups, indicating that specific bacterial strains might be affected by probiotic supplementation.